Organ Transplantation for Foreign Nationals in Canada: A Survey of Transplant Professionals - Greenberg, Rebecca (Can J Kidney Health Dis, 2019)
BACKGROUND: Transplantation for foreign nationals (non-citizens and non-residents) (FNs) in Canada is a complex issue. Currently, there are no Canadian guidelines for the provision of organ transplantation for FNs, and no empirical data on this issue or on transplant professionals’ practices are available. OBJECTIVE: This project aimed to gather empirical data on transplant professionals’ perspectives and practices regarding transplantation for FNs. DESIGN: Survey research design. SETTING: A Web-based survey of members of the Canadian Society of Transplantation (CST). PARTICIPANTS: All members of the CST were invited to participate between April and June 2016. MEASUREMENTS: Multiple-choice questions were developed to capture participants’ attitudes toward different fictitious clinical scenarios in which an FN needed a transplant, their experiences with FNs, their attitude toward FNs in need of transplantation, their knowledge about relevant institutional and organ donation organization (ODO) policies, and their perspectives on a quota. There were two questions with a five-point Likert scale to measure respondents’ agreement with statements related to possible policy options and arguments for and against transplantation for FNs. There was one open-ended question about the content of transplant programs’ policies on transplantation for FNs. METHODS: Descriptive statistical analysis were performed. RESULTS: A total of 87 transplant professionals completed the survey. Over the 4-year period from 2012 to 2016, 47.1% of respondents dealt with at least one situation of listing or performing a transplant for an FN. Only 19.5% of respondents reported that their transplant program had a policy about transplantation for FNs and 59.7% did not know if their ODO had such a policy. When asked about policy options, 47.5% disagreed with a policy of no transplantation for FNs and 41.4% agreed with offering transplantation for FNs in some circumstances (including life-saving and non–life-saving organs). Study participants agreed that transplantation should not be offered to FNs traveling to Canada specifically for transplantation, that FNs should not be transplanted with organs not suitable for Canadian citizens and that there should not be a transplantation quota for FNs. Participants also seem to be more inclined to offer transplantation of life-saving organs, particularly for children. LIMITATIONS: The major limitation of this study is the low response rate of transplant professionals to this survey. CONCLUSION: This is the first study to describe Canadian transplant professionals’ perspectives on transplantation for FNs. The findings of this study will be of interest for future policy development on access to transplantation for FNs. Further studies are needed to gather various key stakeholders’ perspectives on this issue, as well as to analyze the legal and ethical issues and the economics, to develop future policies.